2011
DOI: 10.1007/s00167-010-1387-7
|View full text |Cite
|
Sign up to set email alerts
|

Intra-operative four-stranded hamstring tendon graft diameter evaluation

Abstract: Prospective cross sectional collection of data, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
65
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 19 publications
(36 reference statements)
13
65
5
Order By: Relevance
“…We found that the anthropometric characteristics of our population (mean of height, weight, BMI and graft diameters in our study; 169.1±6.9 cm, 69.2±11.7 kg, 24.1±3.5 and 7.7±0.6 mm) are well matched to previous similar studies [11][12][13][15][16][17][18]. No study in the past has also shown a very strong correlation (R²<0.20) with any of the parameters when multiple stepwise regression analysis was performed [11,13,[16][17][18].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We found that the anthropometric characteristics of our population (mean of height, weight, BMI and graft diameters in our study; 169.1±6.9 cm, 69.2±11.7 kg, 24.1±3.5 and 7.7±0.6 mm) are well matched to previous similar studies [11][12][13][15][16][17][18]. No study in the past has also shown a very strong correlation (R²<0.20) with any of the parameters when multiple stepwise regression analysis was performed [11,13,[16][17][18].…”
Section: Discussionsupporting
confidence: 90%
“…Tuman et al proposed the same threshold for height in their study which was Predicted diameter from equation may agree well with true diameter but with increased risk of over estimating thickness in up to 30 % cases followed up by Treme and colleagues, who further reduced the height for risk of graft less than 7 mm to 140 cm, although both mentioned that this remained more significant for females [11,12]. Ma et al [14] and Pinheiro et al [17] also noted height to be a factor affecting graft diameter for both men and women although women had significantly smaller grafts in their study compared to men and they did not propose a threshold of height for inadequate graft. The findings of Boisvert et al suggested a much taller population statistic with height less than 162.5 cm in women to be a risk for quadrupled graft less than 7 mm but they could not apply it in males; in contrast, Celiktas and colleagues [16,18] proposed 155.2 cm as a height threshold for the men in their study.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…[13] There are some studies that evaluated the graft thickness with the correlations of anthropometric characteristics of the patients. [3,[14][15][16] As an alternative method to anthropometric characteristics in preoperative evaluations, there are some studies based on quantitative analysis in the prediction of intraoperative graft size. And these studies focused on the correlation between CSA and diameter of hamstring tendon on preoperative MRI and intraoperative hamstring graft size.…”
Section: Discussionmentioning
confidence: 99%